Homoepitaxial Diamond Structures with Incorporated SiV Centers. Issue 22 (12th August 2018) - Felgen, Nina; Naydenov, Boris; Jelezko, Fedor; Reithmaier, Johann P.; Popov, Cyril
Abstract : The incorporation of SiV centers during diamond overgrowth on top of partly covered monocrystalline diamond pillars with diameters down to 200 nm are reported. The pillars themselves are prepared via electron beam lithography and inductively coupled plasma reactive ion etching. Then they are covered with a spin‐on‐glass (SOG) (perhydropolysilazane, PHPS) still jutting the apices of the pillars. After a short overgrowth step and removal of the residual SOG the optical investigations reveal the presence of ensembles of SiV centers in the overgrown part of the pillars, a specific location of the centers, and a very strong PL signal. Abstract : Monocrystalline diamond nanopillars, prepared by conventional electron beam lithography and RIE, are covered with a spin‐on‐glass still jutting the apices. After a short overgrowth step and removal of residual spin‐on‐glass the optical investigations reveal the presence of ensembles of SiV centers in the overgrown part of the pillars, a specific location of the centers, and a very strong photoluminescence signal.